Effect of Addition of Duckweed (Lemna sp) and Fish Meal to Feed on Growth and Survival of Nirwana III Tilapia (Oreochromis niloticus) - Kristiana, Indra; Sembiring, Kennedi; Astiyani, Wahyu Puji; Tiawati, Agus (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aimed to determine the effect of duckweed and fish meal on feed on the growth and survival of Nirvana tilapia (Oreochromis niloticus). The tested tilapia were 8-10 cm long and weighed 12 g, kept in 9 aquariums (120 cm x 50 cm x 40 cm), three aquariums as control, three aquariums for treatment A and three aquariums for treatment B, with each each treatment A. 5% dry duckweed and fish meal (1 kg commercial feed, 25 g dry duckweed and 25 g fish meal), treatment B. 5% wet duckweed and fish meal (1 kg commercial feed, 25 g wet duckweed and 25 g g of fish meal) and treatment K (control) without treatment. The results showed that dukweed and fish meal could be used as additional feed for fish. Of the three feeds that gave the best growth, treatment A 5% (dried duckweed and fish meal) had a specific growth rate of 1.7% with a daily growth rate (GR) of 0.32 grams, and an absolute length of 3.16. cm with a survival rate of 99%.